Are fire suppressants “nontoxic”? Acute toxicity, DNA damage and lipid peroxidation in fish (Poecilia reticulata) exposed to low concentrations - de Carvalho, Maysa Ueda [UNESP]; Moreira, Lucas Buruaem [UNESP]; Abessa, Denis Moledo de Souza [UNESP] (Elsevier, 2023)
During an emergency in the Port of Santos (Brazil), large volumes of Aqueous film forming foams (AFFFs) were used, producing an effluent containing a mixture of AFFFs, gasoline and ethanol, which reached the Santos Estuarine System and caused massive fish deaths. This investigation aimed to study the toxicity of three AFFFs (Agefoam; Cold Fire; and F500 Fire) used in the fire fighting on the fish Poecilia reticulata. Acute toxicity tests were conducted using adult individuals, and the lethal concentration to 50% organisms (LC50) was calculated after 96 h, together with the low observed (LOEC) and the no observed effect concentrations (NOEC). Gills and liver from the exposed fish were analyzed for DNA damage and membranes’ lipoperoxidation (LPO). All the AFFFs caused significant fish mortalities, and the LOECs were 0.01% for Agefoam® and 0.001% for F500® and Cold Fire®. Toxicity thresholds were determined for F500® (LC50–48 h = 0.01%), Agefoam® (LC50–96 h = 0.008621%) and the Cold Fire® (LC50–96 h = 0.001221%). Fish exposed to 0.01% and 0.001% of Agefoam® and Cold Fire® did not showed significant effects on DNA damage, while those exposed to F500® presented significantly reduced damages at 0.00001%. The exposed fish presented reduced levels of LPO in most concentrations, excepting those exposed to Cold Fire® (gills) and Agefoam® (liver). The results suggest that the fish deaths were likely caused by direct action of the tensoactives and not by the oxidation induced by reactive oxygen species.
Keywords: Acute toxicity; Aqueous film forming foams; Biochemistry; Fire fighting; Fish